A Novel Protective Logic for Optimal Coordination of Overcurrent Relays - Sajad Samadinasab; Farhad Namdari; Nader Shojaei (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Usually coordination of overcurrent relays is done by taking into account the specific structure of the system which does not show the real state of the system. On the other hand, dynamic changes in network can occur due to short circuit conditions, the malfunctioning relays, development, operation and repairs on any part of the power system. Also the most of the new protective schemes are based on a communication channel, which cannot be guaranteed in practice. Therefore, solving the problem of relay coordination is extremely difficult in case of dynamic changes in the network structure and the absence of communication links between some relays. In this article, a novel protective logic based on phasor measurement units (PMUs) data is proposed for optimal coordination of overcurrent relays. In this method, by using the PMU measurements, phasor information can be obtained continuously at any node where PMUs are installed in the power grid. For this purpose, in the first the Optimal PMU placement is determined for full network observability. Then, the dynamic changes of network will be observe by using wide area measurements based on PMUs data. Finally this information is sent via communication links PMUs for the optimal coordination of overcurrent relays. The use of PMU for the coordination of overcurrent relays improve the decision making capability and performance of protective relays and help them to form a reliable and robust protection system. The proposed method is tested on IEEE 8-bus and 14-bus standard networks.